Research on Optimization Methods of Public Grassroots Governance Based on Big Data Analysis. Issue 4 (April 2021) - Cui, Dandan
Abstract: With the continuous progress of the society and the continuous improvement of the people's level, the social mechanism is gradually sound, people also put forward higher requirements for public grass-roots governance. The development of science and technology, especially the emergence of artificial intelligence, provides convenient conditions for the expansion of the field of big data(BD), and BD analysis is gradually applied to various fields. At present, public grass-roots governance is faced with many difficulties due to its wide scope and complex content. Using BD for analysis provides more convenient conditions for promoting the optimization of public grass-roots governance methods. In recent years, the BD analysis and basic research deepening and expanding public governance scheme, we can conclude the traditional grassroots governance is to stay on the surface, there is no grass-roots level, the optimization study is based on analysis of large data base, only combined with digital information, through data analysis to improve work efficiency and better achieve better control effect. By studying the public grassroots governance based on BD analysis, this paper analyzes the existing problems of public grassroots governance under the background of BD, proposes solutions according to the existing problems, and continuously realizes the optimization of public grassroots governance methods.